Nilai Kondisi Jembatan Di Jalan Nasional Dengan Metode Bridge Management System (Bms) Pada Jembatan Wilayah Sumatra Utara - Garnida, Hendra; Syukri, Muhammad; Rosadi, Rosadi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
With the analysis of the value of condition the bridge, it aims to ensure that the bridges are on the road network are safe for road users.The method used for analyzing bridge condition values ??is the Bridge Management System (BMS) method which has become a general reference for bridge inspections in Indonesia. The Bridge Management System (BMS) method makes it easier to assess bridge conditions to identify damaged elements and structures. So that proper handling of bridge maintenance or repair is obtained. This was done as an effort to maintain optimal bridge performance